Pemanfaatan ampas tebu dan kulit pisang dalam pembuatan kertas serat campuran - Yosephine Allita; Victor Gala; Aning Ayu Citra; Ery Susiany Retnoningtyas (Jurnal Teknik Kimia Indonesia, 2012)
The utilization of sugarcane baggase and banana peel for mixed-fiber-paper production Mixed fiber paper, also known as composite paper, is a paper made of two different fibers that aims to strengthen the paper. In this study, mixed fiber paper for packaging purposes was made by utilizing bagasse pulp and used newsprint pulp. As a binder, banana peel may be used since it contains starch and fiber. The objectives of this research were to study the effect of bagasse pulp composition and newsprint pulp, as well as to determine the mass amount of binder used in producing mixed fiber paper which has both tear resistance and tensile strength suitable for packaging paper. Mixed fiber paper was made by varying the ratio of bagasse pulp and newsprint pulp as follows: 0:100, 10:90, 30:70, 50:50, 70:30, 90:10, and 100:0. The study also carried out variation in binder concentration from banana skin flour of 15, 25, 35, 45, and 55 g/4 L. As results, mixed fiber papers produced in this study have met the requirement of Indonesia National Standard (SNI) of base paper for wrapping (SNI 14-6519-2001). Mixed fiber paper with composition of 30% bagasse pulp and 35 g/4 L banana peel binder concentration has tear resistance of 4,018 kN/m and tensile strength of 20,5 N, although the grammage of all papers is above the standard. Keywords: mixed fiber paper, bagasse pulp, banana peel binder, packaging paperAbstrakKertas serat campuran (atau kertas komposit) merupakan kertas yang terbuat dari dua jenis serat berbeda yang bertujuan untuk memperkuat kertas tersebut. Dalam penelitian ini, pulp ampas tebu dan pulp kertas koran bekas digunakan untuk membuat kertas serat campuran dengan tujuan aplikasi kertas kemasan. Sebagai binder, digunakan kulit pisang yang mengandung pati dan serat. Tujuan penelitian ini adalah untuk mempelajari komposisi pulp ampas tebu dan pulp kertas koran, serta untuk mengetahui massa binder yang digunakan agar dihasilkan kertas serat campuran dengan ketahanan sobek dan kekuatan tarik yang paling sesuai untuk aplikasi kertas kemasan. Proses yang digunakan untuk membuat pulp ampas tebu adalah proses acetosolv. Kertas serat campuran dibuat dengan variasi komposisi pulp ampas tebu dan pulp kertas koran dengan perbandingan 0:100, 10:90, 30:70, 50:50, dan 70:30. Selain itu, dilakukan juga variasi konsentrasi binder kulit pisang sebanyak 15, 25, 35, 45, dan 55 g/4 L. Hasil penelitian menunjukkan bahwa kertas serat campuran yang dihasilkan telah memenuhi standar kertas dasar kertas bungkus berlaminasi sesuai SNI 14-6519-2001. Kertas serat campuran yang dibuat dengan komposisi pulp ampas tebu 30% dan konsentrasi binder 35 g/4 L menghasilkan ketahanan sobek sebesar 4,018 KN/m dan kekuatan tarik sebesar 20,5 N walaupun gramatur kertas lebih besar dari standar yang ditetapkan.Kata kunci: kertas serat campuran, pulp ampas tebu, binder kulit pisang, kertas kemasan